Monitoring external and internal training and match loads in professional soccer players during excessive heat stress - Rabbani, Alireza; Clemente, Filipe Manuel; Banicevic, Zeljko; Banicevic, Ivana; Silva, Rui Miguel (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Purpose. This study explored how heat stress affects training and match load in professional soccer by monitoring ten elite players during sessions under normal (18–24°C) and high (34–45°C) temperatures.Methods. Ten outfield men’s soccer players from a professional team competing in the United Arab Emirates (UAE) Pro League participated in the study. A repeated-measures study design was employed to analyse the training load demands on the same players under normal (18–24°C) and high (34–45°C) temperature conditions throughout the training camp period. External loads, such as total distance (TD), high metabolic load distance (HMLD), mechanical work (MW), and maximal velocity (MaxV), as well as internal load, via Edwards’ Training Impulse (TRIMP), were analysed.Results. The study found that heat influenced training and match loads to varying degrees. On match day (MD), TD per minute (TD · min–1) decreased slightly (effect size [ES] = –0.55), with larger reductions observed on MD-2 (ES = –2.14) and MD-1 (ES = –1.59). Specifically, the reduction in TD.min-1 was greatest on MD-2 and MD-1, while only a small decrease was observed on MD. HMLD per minute (HMLD · min–1) also showed a significant reduction, with a moderate decrease on MD-1 (ES = –1.03) and MD (ES = –0.78). MW per minute (MW · min–1) was notably lower on MD-2 (ES = –1.50), moderately reduced on MD-1 (ES = –0.84), and slightly reduced on MD (ES = –0.45). Maximal velocity (MaxV) slightly increased on MD (ES = 0.47). TRIMP increased across all days, indicating a higher internal load under heat, with a moderate increase on MD-2 (ES = 0.77), MD-1 (ES = 0.73), and MD (ES = 0.83).Conclusions. The study showed the different effects of heat on external and internal training loads, suggesting that while external loads decrease due to the physiological strain of heat, internal load compensates by increasing. This response may indicate a greater effort to maintain performance levels despite heat stress. These findings show that heat-induced changes in training load can help implement strategies for optimising athlete performance and recovery during periods of heat exposure.
Keywords: football; monitoring; sports training; performance; thermoregulation